ENTERPRISE RESOURCE PLANNING AND REAL EARNINGS MANAGEMENT: A STUDY IN INDONESIA - Rokhaniyah, Siti; Simamora, Alex Johanes; Sitoresmi, Mumpuni Wahyudiarti (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
This study examines the effect of Enterprise Resource Planning (ERP) on Real Earnings Management (REM). The sample used was 590 manufacturing firm-years listed on the Indonesia Stock Exchange for 2017-2021. REM is proxied by three abnormal activities: oversales, overproduction, and discretionary expense cutting. The result of the panel data regression analysis indicates that ERP implementation has a significant negative effect on REM. Further, the role of ERP system implementation in reducing REM is more prominent for overproduction, discretionary expenses activities, and suspect firms of beating revenue targets. ERP system is essential for reducing information asymmetry and constraining REM effectively. This study provides implications for firm management in making decisions about ERP investment and improving ERP performance, thereby reducing REM. This study strengthens and extends previous findings about ERP in REM by involving non-ERP implementers as a control group, using alternative ERP implementation periods to control for effectiveness, and also examines the firm's suspect and non-suspect of REM.JEL: M410, M400, M21.